Comparison of various pressure methods along with aspiration in treatment of auricular seroma - Modi, Niral R.; Tota, Sanjay M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Auricular seroma or pseudocyst is soft cystic swelling on the pinna due to collection of intra cartilaginous fluid. The successful management of auricular seroma by aspiration and pressure remains a challenge as this disease has high recurrence rate. Methods: A total 28 patients with auricular seroma were treated by aspiration and different methods of pressure modalities as corrugated rubber splint, button, mastoid dressing and plaster of paris and their results were compared in this study. Results: No any recurrence of seroma and any complication occur after rubber splint pressure application. Post procedure complain like fever, pain, oedema, perichondritis and recurrence are more present in button, mastoid dressing and plaster of Paris pressure application. Conclusions: Aspiration and pressure application with rubber splint provides very simple, minimally invasive and effective management of auricular seroma. It is cost effective give uniform pressure and less traumatic to skin. Pressure with rubber splint method has low recurrence rate and as there is no need of mastoid bandage so less social embracement.